PROSES PRODUKSI VIDEO IKLAN DIGITAL MELALUI MEDIA SOSIAL DI UNIVERSITAS INDONESIA MAJU (Studi Kasus pada Instagram @uimaofficial) - Restu Fajar Maulana (JURNAL ILMIAH NUSANTARA, 2025)
This research examines the digital advertising video production process via Instagram at Universitas Indonesia Maju (UIMA). The study is based on the use of the official Instagram account @uimaofficial as a visual promotional tool for the institution, which, despite its potential, still faces challenges in planning, production execution, and evaluation. The objective is to analyze in detail the stages of pre-production, production, and post-production carried out by UIMA’s marketing team. A qualitative approach with a case study method was employed. Data were collected through participatory observation, structured interviews with the marketing and social media team, and documentation of digital content. The data analysis used Miles and Huberman’s model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that UIMA’s video production process is not yet fully integrated or strategically aligned. Content production remains inconsistent, Instagram features such as Reels and Stories are underutilized, and post-publication evaluations are not systematically conducted. These findings suggest the need for workflow improvements, enhancement of narrative and visual quality, and the application of structured scheduling and evaluation to present video content more effectively.